CHEMICAL AND ORGANOLEPTIC QUALITY OF SMOKED SALTED EGGS WITH THE ADDITION OF HERBAL INGREDIENTS GINGER AND TURMERIC - Salma Sania; Andri Kusmayadi; Putri Dian Wulansari (Universitas Nusa Cendana, 2026)
The addition of herbal ingredients such as turmeric and ginger can increase the durability and shelf life of smoked salted eggs. The active compounds curcumin and gingerol are thought to play a role in increasing the quality of salted eggs. This study aims to analyze the effect of adding turmeric and ginger on the chemical and organoleptic properties of smoked salted eggs. The method used was a Completely Randomized Design (CRD) with four treatments: P0 (control), P1 (turmeric 7.5%), P2 (ginger 7.5%), and P3 (combination of turmeric and ginger 7.5%), each with five replications. The parameters observed included ash content, salt content, crude fiber, and organoleptic tests (color, aroma, texture, and preference). The results showed that the addition of turmeric and/or ginger had a significant effect on ash content, color, aroma and had a very significant effect on crude fiber content, but had no significant effect on salt content, texture and preference level. The mineral and crude fiber content in turmeric and ginger contributed to the increase in ash and crude fiber content. Meanwhile, the addition of turmeric and ginger in the salted egg mixture does not affect the salt content, so the salty taste remains balanced, neither excessive nor lacking. The best results were obtained in the combination treatment of 7.5% turmeric and 7.5% ginger (P3) with an ash content of 12.27%, a salt content of 4.00%, crude fiber of 4.41%, and an organoleptic score for color of 4.07, aroma of 3.60, and a preference level of 3.47. Thus, the use of a combination of turmeric and ginger can be an alternative in improving the quality and durability of smoked salted eggs without changing the balance of taste.